Marshal Koněv and the Immaculate Virgin: Some Art-Historical Issues in the Czech Politics of Memory - Bartlová, Milena (Dějiny – teorie – kritika, 2021)
The contribution explores recent conflicts concerning public monuments in the Czech context. It looks in detail at two specific cases, namely the removal of the bronze figure of Soviet Marshal Koněv in Prague Bubeneč and the erection of a copy of the Baroque Marian Column at the Old Town Square in Prague. In both cases, the root context is political: post-Communism and the social memory of the recent past in the case of Marshal Koněv, and post-secular demands from part of the Catholic Church to acquire more political influence in the case of the Marian Column. While art historical judgments have also played a key part in the debates surrounding both cases, these have been used only superficially and instrumentally: there has not been any in-depth critical discussion about these cases within the theoretical framework of art history as an academic discipline. Keywords: public monuments, politics of memory, Prague monuments, artistic quality, Czechoslovak culture 1948-1989.